A nested PCR assay exhibits enhanced sensitivity for detection of Theileria parva infections in bovine blood samples from carrier animals - Odongo, David O.; Sunter, J.D.; Kiara, Henry K.; Skilton, Robert A.; Bishop, Richard P. (Springer, 2010)
Theileria parva causes East Coast fever, an economically important disease of cattle in sub-Saharan Africa. We describe a nested polymerase chain reaction (nPCR) assay for the detection of T. parva DNA in cattle blood spotted onto filter paper using primers derived from the T. parva-specific 104-kDa antigen (p104) gene. The sensitivity of this assay was compared to a previously described p104-based PCR and also the reverse line blot (RLB) technique, using serial dilutions of blood from a calf with known T. parva piroplasm parasitaemia. The relative sensitivities of the three assays were 0.4, 1.4 and 4 parasites/µl corresponding to blood parasitaemias of 9.2 × 10−6%, 2.8 × 10−5% and 8.3 × 10−5%, respectively. The three assays were applied to samples from two calves infected with the T. parva Muguga stock. Parasite DNA was consistently detectable by the two p104 PCR assays until 48 and 82 days post-infection, respectively, and thereafter sporadically. RLB detected parasite DNA in the two infected calves until days 43 and 45. Field samples from 151 Kenyan cattle exhibited 37.7% positivity for T. parva by regular p104 PCR and 42.3% positivity using p104 nPCR. Among 169 cattle blood samples from Southern Sudan, 36% were positive for T. parva using nPCR. The nPCR assay represents a highly sensitive tool for detection and monitoring of asymptomatic carrier state infections of T. parva in the blood of cattle.